Predictors of Perceived Changes in Psychological Wellbeing among Clergy in the USA Serving in the Episcopal Church during the 2021 Covid-19 Pandemic - Francis, Leslie J. (Journal of Anglican studies, 2025)
Applying the balanced affect model of clergy psychological wellbeing, as conceptualised by the Francis Burnout Inventory (FBI) and operationalised by The Index of Balanced Affect Change (TIBACh), this study explored the impact of seven sets of variables on individual differences in perceived changes in positive affect and negative affect among 737 clergy in the USA serving in the Episcopal Church during the Covid-19 pandemic. The seven sets of variables were: personal, psychological, contextual, ministry-related, church orientation, theological stance, and attitudinal. The data supported the balanced affect model of clergy psychological wellbeing by demonstrating how different variables predicted individual differences in negative affect and in positive affect. For example, clergywomen showed no differences from clergymen in terms of positive affect, but higher levels of negative affect; active self-supporting and retired clergy showed no differences from stipendiary clergy in terms of positive affect, but lower levels of negative affect; Evangelical clergy showed no differences in negative affect, but higher levels in positive affect. The balanced affect model provides insights into how clergy may be better supported during a pandemic.